2021
DOI: 10.1001/jamahealthforum.2020.1613
|View full text |Cite
|
Sign up to set email alerts
|

Projections of US Prescription Drug Spending and Key Policy Implications

Abstract: The most recent Centers for Medicare & Medicaid Services (CMS) projection of national health expenditures (NHE) 1 was released in March 2020, covering 2019 through 2028. CMS projects that retail prescription drug spending will represent about 9% of NHE over this period. (In December, CMS released the 2019 NHE. At $369.7 billion, retail prescription drug spending increased 5.7%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…As with many electronic health record (EHR)-based and other tools, there are important implementation considerations that influence the success of RTBTs in practice. 2 In this issue of the journal, Desai et al 3 present findings from a cluster randomized evaluation of one institution's experience with RTBTs. They found that RTBTs could be used for a small minority (4%) of prescription orders and their use was associated with an 11% reduction in out-of-pocket costs when prescribers were shown lowercost choices via the EHR.…”
Section: Role Of the Funder/sponsormentioning
confidence: 99%
See 2 more Smart Citations
“…As with many electronic health record (EHR)-based and other tools, there are important implementation considerations that influence the success of RTBTs in practice. 2 In this issue of the journal, Desai et al 3 present findings from a cluster randomized evaluation of one institution's experience with RTBTs. They found that RTBTs could be used for a small minority (4%) of prescription orders and their use was associated with an 11% reduction in out-of-pocket costs when prescribers were shown lowercost choices via the EHR.…”
Section: Role Of the Funder/sponsormentioning
confidence: 99%
“…Rising drug costs are placing more financial burden on patients . High out-of-pocket costs contribute to decreased medication adherence, poor health outcomes, and higher overall health care spending .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonretail drugs—those administered in medical settings rather than used at home—accounted for about one-third of US prescription drug spending in 2018. 1 Costs for these drugs are projected to increase faster than retail drugs. 2 The majority of cancer drugs are delivered in health care settings.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutical expenditures, which account for approximately one-sixth of the total health expenditures in developed countries (Organization for Economic Co-operation and Development [OECD], 2021), are one of the most important expense items of the Social Security Institution in Turkey (Çalışma ve Sosyal Güvenlik Bakanlığı [ÇSGB], 2021). It has been reported that pharmaceutical expenditures have increased significantly over the last decade, mainly due to expenditures on prescription drugs, increased use, and the introduction of new and costly drugs (Conti et al, 2021;DeMartino et al, 2021). For this reason, countries should control pharmaceutical expenditures and take the necessary precautions.…”
Section: Introductionmentioning
confidence: 99%